AKSELERASI PENINGKATAN KOMPETENSI PENDIDIK DAN TENAGA KEPENDIDIKAN NONFORMAL - Enceng Mulyana (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
This article discusses various steps to increase the competence of PTK-PNF. First, it describes the roles of non-formal education in the national education system and the existing problems in the non-formal education. Then, the strategies to accelerate the competencies of PTK-PNF are introduced to cover the basic competencies and mapping of PTK-PNF. Further, the model of acceleration and need analysis to improve the competencies of PTK-PNF and the model of controlling the quality of the competence are elaborated and a set of controlling principles are identified. The article concludes that accelerating the competencies of PTK-PNF is an urgent need and can not be avoided to achieve the objectives of national education. This could be done through pre-service training, inand on-service trainings or distance learning programs. Total Quality Management and Professional Approach are recommended to be implemented continuously in each program.